Granulometry based Extrapolation of Depositional Environment of Orangi Sandstone, Nari Formation Exposed around Hub Dam, Pakistan - Bashir, Erum; Khaleeq, Sadia; Naseem, Shahid; Kaleem, Maria; Shumail, Muhamad; Ahmed, Wajih (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2025)
To infer the depositional environment, thirty-eight samples of the Orangi Sandstone-the uppermost unit of the Upper Oligocene Nari Formation, exposed at Hub Dam were collected. Granulometric data acquired from standard sieving techniques. The computed graphic mean's average value, was 1.38. Of the 38 samples, 24 were categorized as medium-grained, and the remaining 14 as coarse-grained. According to the sorting values, 36.84% of the samples were categorized as moderately sorted to moderately well-sorted, whereas 63.15% of the samples were poorly sorted. Skewness values showed a wide range from -2.17 to 2.65 suggesting a mixed population of coarse and fine skewed sediments. Kurtosis ranged from -2.46 to 2.97, showed situation of both leptokurtic and platykurtic. Bivariate plots created employing various textural parameters suggested predominantly fluvial origin with very few deviations. This interpretation is further supported by linear discriminant function analysis, which indicates a fluvial to shallow marine depositional setting for most samples. The study represents an initial attempt to appraise the vertical and lateral variability of the Orangi Sandstone using cement composition and textural parameters; skewness and kurtosis. The studied samples significantly reflect the impact of Upper Oligocene Period's tectonics, climate shift, and sea level fluctuations, and sediment transport dynamics. A model is constructed to describe the preponderant fluvial environment outlining the role of beach and tidal processes along with fluvial channels in the deposition of the sandstone.